2003
DOI: 10.1086/377203
|View full text |Cite
|
Sign up to set email alerts
|

Three Days of Intravenous Benzyl Penicillin Treatment of Meningococcal Disease in Adults

Abstract: New Zealand has experienced an epidemic of predominantly serogroup B meningococcal disease during the past decade. In a prospective study, we treated adults (age, >15 years) with meningococcal disease with intravenous benzyl penicillin (12 MU [7.2 g] per day) for 3 days. Sixty-one adults with suspected meningococcal disease were consecutively admitted during the 33-month period; 3 patients were excluded. The 58 patients had a mean age (+/- standard deviation [SD]) of 27.9+/-14.5 years (median, 21 years; range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 34 publications
(34 reference statements)
0
14
0
1
Order By: Relevance
“…The standard duration of therapy for meningococcal infection is 7 days. A shorter regimen is useful in developing countries, and several researchers have shown that 3 days of intravenous treatment with Penicillin G is effective (68). Treatment with single doses of both ceftriaxone and chloramphenicol resulted in a good outcome in a meningococcal meningitis epidemic in Niger, with a mortality of approximately 5% (69).…”
Section: Treatmentmentioning
confidence: 99%
“…The standard duration of therapy for meningococcal infection is 7 days. A shorter regimen is useful in developing countries, and several researchers have shown that 3 days of intravenous treatment with Penicillin G is effective (68). Treatment with single doses of both ceftriaxone and chloramphenicol resulted in a good outcome in a meningococcal meningitis epidemic in Niger, with a mortality of approximately 5% (69).…”
Section: Treatmentmentioning
confidence: 99%
“…Six patients (7%) died, four of those while receiving treatment and there were no relapses. An additional prospective series, but not a randomised study, from the same New Zealand group [9] included 44 patients with confirmed, and 14 with probable, meningococcal disease. The mean age of the patients was 27.9 + 14.5 years, the median time before presentation to the hospital was 24 h (9-168 h), 81% had rash, 67% fever, 43% systemic inflammatory response syndrome (SIRS), 10% had severe sepsis and 21% septic shock.…”
Section: Meningococcal Meningitismentioning
confidence: 99%
“…When antibiotic sensitivities become available, antibiotic therapy can be guided by these results, but careful consideration should be given to those antibiotics with adequate minimal inhibitory concentration. The recommended duration of antibiotic treatment is 7 days, but recent studies suggest that CSF sterilization may occur within 3 days to 4 days [18]. In our practice, we use ceftriaxone for treatment of MD and MM (Table 1).…”
Section: Antibiotic Therapymentioning
confidence: 99%